Model-Model Pembelajaran Ilmu Fara’idh - Nurjanah, Tati (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2019)
This study aims to elaborate learning models of ilmu farâ'id. This study uses library research methods. The model is a plan, representation or description that describes an object, system or concept that is often in the form of simplification or idealization. Learning can be said as a result of memory, cognition, and metacognition that affects understanding. This happens when someone is learning, and this condition also often occurs in everyday life, because learning is a natural process for everyone. In general, the learning model is a method or systematic presentation technique used by the teacher in organizing the experience of the learning process in order to achieve the objectives of a learning. The study of farâ’idh includes interactive learning, card sort strategies, CTL (contextual teaching and learning), Al-Farâidh Android-based and lecture methods, questions and answers, memorization, assignments, discussions, problem solving, demonstrations, and constructivism methods. The science of farâ’idh or also called the science of mawaris is the science of the distribution of inheritance after a person dies or dies. This science regulates the problem of the distribution of inheritance for heirs in accordance with the provisions that have been written in the Qur'an. Another similar opinion explains that the science of farâ’idh is a science so that every Muslim knows who has the right to receive inheritance and those who do not have to receive inheritance, as well as what price or value is received by the heirs and how they are distributed.